Paediatric doses during some common X-ray procedures at selected referral hospitals in Tanzania - Muhogora, W. (Radiat Prot Dosimetry, 2016)
The aim of this study was to determine the radiation doses to paediatric patients of different age groups at three large hospitals for optimisation purposes. The entrance surface air kerma (ESAK) values were determined from the measured X-ray output values using calibrated ionisation chamber, TW 233612 and clinical patient parameters. The air kerma-area product (KAP) values were measured using a calibrated Diamentor E2 system. The volume computed tomography dose index (CTDI(vol)) and dose length product (DLP) values were obtained from the computed tomography (CT) equipment verified by a calibrated CT chamber, Unifors Xi CT. Irrespective of age groups, the results show that the median ESAK values ranged from 62.6 to 248.1 µGy. The median KAP values ranged from 135.6 to 1612 µGy cm(2), while the median DLP values ranged from 119.1 to 600 mGy cm. Analysis of the results indicates that optimisation can be achieved through good practice awareness and patient dose and image quality evaluations.